2014
DOI: 10.1177/1535370214551693
|View full text |Cite
|
Sign up to set email alerts
|

The supplementation of Korean mistletoe water extracts reduces hot flushes, dyslipidemia, hepatic steatosis, and muscle loss in ovariectomized rats

Abstract: Since Korean mistletoe (Viscum album) has been used for alleviating metabolic diseases, it may also prevent the impairment of energy, glucose, lipid, and bone metabolisms in an estrogen-deficient animal model. We determined that long-term consumption of Korean mistletoe water extract (KME) can alleviate menopausal symptoms such as hot flush, increased abdominal fat mass, dyslipidemia, hyperglycemia, and decreased bone mineral density in ovariectomized (OVX) rats fed a high-fat diet, and explored the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…The present study showed that both HE and EE of T. foenumgraecum seed are able to improve metabolic status and decrease level of these cytokines in ovariectomized rats. Ovariectomy is a standard experimental model of menopause in rodent to investigate pharmacological management of postmenopausal symptoms (11,12,24,25). In our study, in agreement with previous reports, ovariectomy led to increased body weight gain (25,26).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study showed that both HE and EE of T. foenumgraecum seed are able to improve metabolic status and decrease level of these cytokines in ovariectomized rats. Ovariectomy is a standard experimental model of menopause in rodent to investigate pharmacological management of postmenopausal symptoms (11,12,24,25). In our study, in agreement with previous reports, ovariectomy led to increased body weight gain (25,26).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, development of new agents with anti-inflammatory action and lesser side effects for management of menopause remains an attractive subject. It has been reported that a number of medicinal plants may be useful for preventing or treating some menopausal related complications such as insulin resistance, dyslipidemia, hepatic steatosis, weight gain, inflammation, and loss of bone mass (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…19,31 HT reverses most symptoms, but also induces some adverse effects. Estrogen deficiency is also recognized to induce degenerative changes in articular cartilage and subchondral bone, and estrogen replacement delays the changes by acting on estrogen receptors in the articular cartilages, synovial membrane, and ligaments in animal studies.…”
Section: Yang Et Almentioning
confidence: 95%
“…The dosages of lyophilized water KME and UCE were determined by our preliminary and previous studies 19 : each test diet contained 0.6% KME or 2% UCE in a high-fat diet. In our preliminary study, low dosages (0.5-2 mg/mL) treatment of KME lowered tumor necrosis factor-a (TNF-a) expression in lipopolysaccharide-activated RAW 264.7 cells (mouse leukemic monocyte/macrophage cell line).…”
Section: Diet Preparationmentioning
confidence: 99%
“…Recent studies have reported that long-term oral consumption of water extract from the Korean mistletoe Viscum album in ovariectomized rats (an oestrogendeficient model of post-menopausal stage) alleviates menopausal symptoms and modulates glucose and lipid metabolism (Kim et al, 2015). The anti-osteoporosis effects of aqueous-methanol extracts of the Eastern Nigerian mistletoe Lorantus micrantus have also been described (Omeje et al, 2014).…”
Section: Introductionmentioning
confidence: 99%